The financial burden of COVID-19 hospitalization: A retrospective economic evaluation - Putro, Wahyu Gito (Svāsthya: Trends in General Medicine and Public Health, 2025)
The COVID-19 pandemic continues to demonstrate dynamic fluctuations across global, regional, and local contexts. These ongoing variations have substantial public health and socioeconomic consequences worldwide. This study examines the financial and demographic effects of COVID-19 hospitalizations at South Tangerang General Hospital between 2021 and 2022. A retrospective economic analysis by comparing hospitalization data from 2021 and 2022. This study evaluated key parameters, including patient demographics, duration of hospitalization, treatment costs, and funding sources, identifying significant patterns across the study period. This study revealed notable changes in patient demographics, with the predominant age group shifting from > 59 years (2021) to 19-59 years (2022; p=0.000). The percentage of females represented increased from 49.1% to 59.5% (p=0.033). Compared with 2021 admissions, hospital stays were significantly shorter, with most 2022 patients discharged within 1–5 days (p=0.000). The average treatment costs declined from $3,676 to $2,024 (p=0.000), primarily due to reduced nursing and medication expenses. Funding sources transitioned from near-total (99.6%) reliance on the national COVID-19 program in 2021 to 52.7% coverage by the BPJS health insurance in 2022 (p=0.000). This study revealed significant changes in COVID-19 hospitalization patterns, characterized by younger patient populations, shorter hospital stays, and lower treatment costs. The evolving financial model, which incorporates both insurance and government support, highlights the necessity of forward-looking financial strategies in healthcare systems to effectively manage future health crises. These findings underscore the adaptive capacity of the healthcare sector and the critical role of socioeconomic considerations in treatment outcomes.